Are We There Yet? - A Systematic Literature Review on Chatbots in Education - Wollny, Sebastian; Schneider, Jan; Di Mitri, Daniele; Weidlich, Joshua; Rittberger, Marc; Drachsler, Hendrik (Frontiers in Artificial Intelligence, 2021)
Chatbots are a promising technology with the potential to enhance workplaces and everyday life. In terms of scalability and accessibility, they also offer unique possibilities as communication and information tools for digital learning. In this paper, we present a systematic literature review investigating the areas of education where chatbots have already been applied, explore the pedagogical roles of chatbots, the use of chatbots for mentoring purposes, and their potential to personalize education. We conducted a preliminary analysis of 2678 publications to perform this literature review, which allowed us to identify 74 relevant publications for chatbots’ application in education. Through this, we address five research questions that, together, allow us to explore the current state-of-the-art of this educational technology. We conclude our systematic review by pointing to three main research challenges: 1. Aligning chatbot evaluations with implementation objectives, 2. Exploring the potential of chatbots for mentoring students, and 3. Exploring and leveraging adaptation capabilities of chatbots. For all three challenges, we discuss opportunities for future research.